A culture-centered exploration of India’s Community Health Workers’ meanings of the COVID-19 pandemic and the role of mobile technology in response strategies : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Communication and Journalism at Massey University, Te Kunenga ki Pūrehuroa, Center for Culture-Centered Approach to Research and Evaluation (CARE) - Pattanaik, Samiksha (Massey University, 2025)
During the COVID-19 pandemic, Community Health Workers (CHWs), particularly in developing countries such as India, played a crucial role in controlling the virus's spread (Niyati & Nelson Mandela, 2020). India imposed the world’s largest lockdown (Ghosh, 2020; Mathur, 2020), swiftly deploying its CHWs known as ASHA workers for community-level COVID-19 prevention and mitigation (Niyati & Nelson Mandela, 2020). Reports indicated that ASHAs in some states were required to purchase and use smartphones for COVID-19 tasks (Brar Singh, 2020; Hindustan Times, 2020b). This top-down approach to pandemic communication and mHealth initiatives (M. J. Dutta, S. Kaur-Gill, et al., 2018; Kumar & Anderson, 2015) sidelined ASHAs' their voices in mainstream discourse, despite their essential role. Furthermore, while existing research in this area has identified the structural challenges faced by ASHAs—such as overwhelming workloads and inadequate compensation—these studies often treat these challenges in a reductionist manner (Lazarus, 2020; Nichols et al., 2022; Srivastava, 2021), often from the perspective of the researcher. This marginalisation of ASHAs' voices is particularly concerning in the context of public health emergencies, where they are thrust into frontline roles without adequate infrastructural and policy support. This thesis addresses this significant gap in research by foregrounding their voices and lived experiences as frontline workers during the COVID-19 pandemic. Drawing on the Culture Centered Approach (CCA), a meta-theoretical framework particularly suited for research in marginalised settings, this study uses semi-structured interviews to explore ASHAs’ narratives, shedding light on how they navigated the pandemic and engaged with mHealth initiatives. The study finds that ASHAs operate within intersecting layers of structural inequalities shaped by their socio-economic context and the neoliberal organisation of India’s healthcare system. This system reduces these marginalised female workers to ‘efficient’ subjects, using their labour to offload state responsibilities while offering minimal support and compensation. Through this analysis, the research advances the theoretical framework of the CCA by deepening the understanding of the layering of structures upon structures and their simultaneous interaction with culture. While existing CCA literature addresses the structure culture dynamic, this study uniquely highlights how these layered structures intersect, reinforce, and sometimes contradict each other, intensifying marginalisation. In the context of mHealth, the study uncovers the complex, multifaceted, and sometimes contradictory meanings of technology in marginalised spaces, ranging from the relevance of face-to-face communication and bottom-up uses of technology in rural healthcare, to issues surrounding data privacy, confidentiality, and digital burden in marginalised spaces. By placing these evolving and often contradictory meanings at the center of theorising, this research challenges techno-optimism and prompts a critical re-evaluation of the role of technology in healthcare delivery, with mHealth as a key example. Additionally, this study extends the concept of marginalised agency within the CCA by shifting away from binary understandings of resistance and submission, demonstrating how such agency is multidimensional and dynamic, shaped by an intricate web of cultural, social, religious, economic, and professional factors. This multilayered interaction forces ASHAs to continuously negotiate their positions, sometimes exercising their voices and demands, and at other times complying with top-down orders due to structural constraints, while drawing on cultural resources to navigate these structures. The thesis concludes with recommendations for a communicative framework that integrates ASHAs into decision-making processes, fostering resilience among CHWs and the communities they serve in future health crises.
Keywords: pandemic communication, COVID-19 pandemic, community health workers, mHealth; Community health aides; India; Attitudes; Community health services; Decision making; Wireless communication systems in medical care; Evaluation; COVID-19 (Disease); Prevention; 420321 Rural and remote health services